A packaging and delivery system for aerial release of Phytoseiidae for biological control - Drukker, B.; Yaninek, J.S.; Herren, H.R. (1993)
A new packaging system for the aerial release of phytoseiids was designed and tested in the laboratory and in the field. The observed escapes before and after release, mortality during all stages of release, and fecundity after release indicated that the system was suitable for transporting and distributing phytoseiids. Other evaluated properties of the packaging system included container opening efficiency, container dispersion over the field at several fly-over altitudes, and the probability of containers to be lodged in the cassava canopy. Aerial release trials followed by recoveries of viable adult female phytoseiids from the target fields demonstrated the feasibility of aerial releases as a means for distributing phytoseiid natural enemies.